Economic and political performances of EU candidate countries from the WB: A quantitative approach of the analysis - Elena Polo; Doris Koliqi Malaj (SPOUDAI - Journal of Economics and Business, 2021)
EU integration is a strategic priority and a clear perspective for 4 countries of the Western Balkans region, currently holding the status of the candidate country. Fulfilment of the Copenhagen criteria has played an increased role in the discussions of the EU accession and enlargement (regularly assessed in the EC progress reports), and depth of monitoring has increased further. Objective of this paper is to assess the political and economic performance of the EU candidates from the WB based on a comparative quantitative analysis through a series of indicators. Despite of the method used, results of the analysis show that there are no significant differences between the candidate countries in improving their political and economic systems, and no major changes in time at the country level, in order to support a sustainable performance and progress. This comprehensive quantitative analysis gave us some key interesting insights about these countries individual performance and the pathway dynamics in their attempts to meet the EU criteria through relevant reforms and policy measures. Given the internal characteristics of EU integration processes (closely linked to EU dynamics, complex political and economic processes/forces, different timing), a qualitative analysis remains crucial for providing an in-depth country-oriented analysis.
Keywords: O52; P48; Y10; 330; EU integration; Western Balkans; Copenhagen criteria; quantitative analysis